Analysis Of The Impact Of The Semi-Fowler Position On Oxygen Levels And Breathing Frequency In CKD Patients within The Emergency Departement Of Rs Sint Carolus Jakarta - Elfrida Jennifer Crystella; Maria Astrid (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Chronic kidney disease, which involves lasting impairment of kidney function, can cause respiratory issues among various other systemic complications. Breathlessness is a common symptom that patients face, and if it goes unaddressed, it can worsen their overall health condition.. Objectives: The aim of this study is to assess the effectiveness of the semi-Fowler position in boosting oxygen saturation and decreasing the respiratory rate in chronic kidney disease patients receiving treatment in the Emergency Department. Methods: This investigation adopted a descriptive case study method focusing on two individuals who experienced breathing difficulties due to chronic kidney disease. Interventions included the provision of oxygen and repositioning the patients into the semi-Fowler position for four hours of monitoring. The gathered data included oxygen saturation levels and respiratory rates measured before and after the intervention. Results: After being positioned in the semi-Fowler setup, both patients exhibited notable improvements in oxygen saturation and reductions in respiratory rates. Oxygen saturation levels rose from 83–94% to 99–100%, while the respiratory rate declined from 30–32 breaths per minute to 26–28 breaths per minute. Conclusions: Positioning patients in the semi-Fowler posture has been shown to effectively enhance respiratory function in individuals with chronic kidney disease within the emergency setting. This method can serve as a first-line non-invasive nursing intervention to promote patient comfort and help maintain the stability of their condition.